The Influence of Transformation Leadership and Ability to Reduce Waste and Intervening Variables of Empowerment are Impact to The Performance of Logistic Department Staff in Asian Alliance International Company Limited - Thurapang, Wannachai; Jadesadalug, Viroj (Journal of Innovation and Management, 2020)
The objectives of this research were (1) to study the influence of the transformation leadership with ability to waste reduction, (2) to study the influence of social empowerment between transformation leadership with ability to waste reduction, (3) to study the influence of psychological empowerment between transformation leadership with ability to waste reduction, and (4) to study the influence of ability to waste reduction with performance efficiency of employees in Logistic Department, Asian Alliance International Co., Ltd. The sample group consisted of 892 employees using stratified random sampling by divisions. This research was a quantitative research. Regression analysis was applied for data analysis to find out influencing variables. The findings revealed that transformation leadership have positive influence on ability to waste reduction. Moreover, ability to waste reduction also have positive influence on performance efficiency of the employees. In addition, the study of 2 moderator variables, social empowerment and psychological empowerment, indicated that both are moderator variables and have negative influence on ability to waste reduction. From the research, the organization should support the development of transformation leadership because it will benefit the organization. To reduce the loss to the organization and will lead to an increase in efficiency in the organization